DAMPAK GREEN MARKETING TOOLS TERHADAP PEMBELIAN PRODUK THE BODY SHOP - Sutisna, Felix; Jap, Yustina Peniyanti (STIE Wiyatamandala, 2023)
The purpose of this research is to analyze the effect of green marketing tools on the decision behavior to buy green products mediated by the intention to buy green products. There are five variables in this study, namely ecological brand image, ecological labeling, ecological advertisement, purchase intention and buying decision behavior. The sample of this research is 274 consumers of The Body Shop. The method of analysis of this research is Partial Least Squares (PLS) analysis. Partial least squares (PLS) analysis was performed using secondary data collection and hypothesis testing. The study concluded that among green marketing tools, only environmental advertising did not have a significant impact on the decision behavior to buy green products, either directly or indirectly.